Transformasi Paradigma Ekonomi UMKM Dari Kapitalistik Menuju Ekonomi Hijau Berbasis Nilai Islam - Ummi Kaltsum Karunianing Utami; Ahmad Habibi; Muhammad Iqbal Fasa (Advances In Education Journal, 2025)
The transformation of economic paradigms among Micro, Small, and Medium Enterprises (MSMEs) has become a critical issue within Indonesia’s evolving economic landscape, particularly as profit–centered capitalist models increasingly reveal their limitations in fostering long-term sustainability. This conceptual article examines the shift of MSMEs from a capitalistic orientation toward a green economy grounded in Islamic ethical values. The transformation is driven by several key factors, including the rising awareness of halal and ethical business practices among Muslim consumers (OJK, 2024), rapid growth in Islamic financial institutions such as Islamic banks, sharia fintech, and BMTs (KNEKS, 2024), regulatory reinforcement through the Financial Sector Development Law and DSN-MUI fatwas, and the expansion of the global halal market valued at over USD 5 trillion (DinarStandard, 2023). Despite these opportunities, the transition of MSMEs toward sharia-compliant and green economic practices faces significant challenges. These include low levels of Islamic financial literacy (Bank Indonesia, 2023), limited access to affordable sharia financing, and gaps in technical guidance and mentorship. To address these issues, this study proposes a four-stage paradigm shift model: value internalization, preparatory business auditing, transformation through the application of sharia contracts and ethical business conduct, and reinforcement through halal certification and sharia-based digitalization. The analysis builds upon previous studies demonstrating the impact of Islamic values on MSME sustainability (Rahman & Rosman, 2022; Zainuddin, 2021) and the alignment between green economy principles and maqāṣid al-sharī‘ah (UNDP, 2022; Nasr, 2014). The findings of this conceptual study indicate that integrating Islamic values, green sustainability principles, and MSME business practices can produce an alternative economic model that is ethically driven, resilient, and globally competitive. This article provides a foundation for policy formulation related to sharia literacy enhancement, expansion of green-sharia financing, and strengthening the national halal ecosystem as a strategic pathway for transforming Indonesia’s MSMEs toward a more just and sustainable economy. Keywords: MSMEs, Islamic economics, capitalism, green economy, paradigm transformation, sustainability.